As fontes de mudança da eficiência técnica da indústria brasileira após a liberalização comercial: uma estimação econométrica por dados de plantas - Andre Nassif (Economia Aplicada, 2005)
This paper presents empirical evidence about the effects of trade liberalization on the evolution of the technical efficiency ofthe Brazilian manufacturing plants. A. panel data regression model is applied to estimate the changes in labor productivity and real average costs at the plant-level between 1988 and 1994, and between 1994 and 1998. The methodology, originally proposed by James Tybout and Daniel Westbrook (1995), was modified to allow more consistent responses to a central question of the academic debate in Brazil throughout the 1990's, that is, which ofthe following potential sources played the main role in productivity gains in the Brazilian manufacturing sector after trade liberalization: i) a cut in employment (employment effect); ii) output-share reallocations among plants within each industry (marketshare effect); or iii) technical innovations, access to foreign equipment through imports, positive economic externalities, among other factors not observed by the researcher (residual effects)? This paper represents an attempt to provide consistent answers to the above questions in the case of recent Brazilian experience. It provides evidence that the first effect prevailed over the others in explaining the technical efficiency gains ofthe Brazilian manufacturing sector throughout the 1990's.